How does psychosocial safety climate affect safety behavior in the construction industry? A cross-level analysis - Wei Zhao; Shuquan Li (Frontiers Media S.A., 2024)
IntroductionThe unsafe work of construction workers directly contributes to frequent accidents in workplaces. However, the factors influencing the safety behavior of Chinese construction workers are not yet clear.MethodsData from 381 construction workers were analyzed to test our hypotheses.This study aimed to investigate the impact of psychosocial safety climate (PSC) on safety behavior through a cross-level model, focusing on the mediating role of psychological resilience and the moderating effect of safety-related stress.ResultsThe results indicated that (1) PSC was positively associated with psychological resilience and safety behavior; (2) psychological resilience mediated the relationship between PSC and safety behavior; (3) the link between PSC and safety behavior was negatively influenced by safety-related stress; and (4) all three sub-dimensions of safety-related stress moderated the effect of PSC on safety participation.DiscussionThese findings elucidate the mechanisms underlying the connection between PSC, psychological resilience, safety-related stress, and safety behavior from a multi-level perspective. Additionally, strategies for enhancing the safety behavior of construction workers were discussed.